2020
DOI: 10.1111/his.14254
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre analytical comparison study of inter‐reader and inter‐assay agreement of four programmed death‐ligand 1 immunohistochemistry assays for scoring in triple‐negative breast cancer

Abstract: Aims Studies in various cancer types have demonstrated discordance between results from different programmed death‐ligand 1 (PD‐L1) assays. Here, we compare the reproducibility and analytical concordance of four clinically developed assays for assessing PD‐L1‐positivity in tumour‐infiltrating immune cells in the tumour area (PD‐L1‐IC‐positivity) in triple‐negative breast cancer (TNBC). Methods and results Primary TNBC resection specimens (n = 30) were selected based on their PD‐L1‐IC‐positivity per VENTANA SP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“… 4 The only published study investigating SP142 PD-L1 interobserver agreement in TNBCs enriched around the 1% cutpoint reported an interclass correlation coefficient of 0.805 among 7 specifically trained pathologists in a limited cohort of cases (n=30). 5 …”
mentioning
confidence: 99%
“… 4 The only published study investigating SP142 PD-L1 interobserver agreement in TNBCs enriched around the 1% cutpoint reported an interclass correlation coefficient of 0.805 among 7 specifically trained pathologists in a limited cohort of cases (n=30). 5 …”
mentioning
confidence: 99%
“…Table 8 summarizes the comparisons of PD-L1 expression on ICs using different antibodies according to the results of previous studies and the present one. The rates of PD-L1 expression were relatively different among these studies [21][22][23][24][25]. The PD-L1 positivity rates using the SP142 assay ranged from 19.3% to 67.7% and those using the 22C3 assay ranged from 32.6% to 81% (the 22C3 assay was analyzed by a combined positive score).…”
Section: Discussionmentioning
confidence: 91%
“…The IMpassion130 trial clearly demonstrated that atezolizumab plus nab-paclitaxel significantly prolonged progression-free survival in advanced or metastatic PD-L1-positive TNBC patients [11]; the study defined PD-L1-positivity as PD-L1-expressing ICs �1% in the tumor area [11], which is the same definition used in this study. However, various immunohistochemical platforms have been developed to evaluate PD-L1 expression; thus, few studies have compared the differences between all the PD-L1 immunohistochemical assays in TNBC tissues [21][22][23][24][25]. For example, the 73-10 assay, which is the companion diagnostic tests for avelumab [16,36], has not yet been analyzed in TNBC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we evaluated the level of concordance and spatial heterogeneity of PD-L1 expression using a multi-level methods approach, demonstrating substantial discordance among the different methodologies. In comparison, previous comparative studies have been limited in that they mostly evaluated the PD-L1 IHC expression using different antibody clones with the sole focus on TNBC [ 22 , 23 ]. In line with previous results [ 6 ], we show here that PD-L1 positivity was highly concordant between SP142 and SP263 immunohistochemical antibodies, while the observed level of discordance varied depending on the applied method.…”
Section: Discussionmentioning
confidence: 99%